The Conceptualization of Professional Nurse Autonomy - Supametaporn, Pinhatai (Nursing Science Journal of Thailand, 2013)
Professional nurse autonomy is considered an essential component for nursing performance and professional development, but little is known about the advancement of this concept in Thailand. The purpose of this article was to analyze and synthesize the concept based on the existing literatures. Factors affecting professional nurse autonomy and instruments used to measure this construct are also explored. The findings clarified the boundary, characteristics and source of professional nurse autonomy. Keywords: autonomy, professional nurse บทคัดย่อ: เอกสิทธิ์แห่งวิชาชีพพยาบาล เป็นองค์ประกอบที่สำคัญของการปฏิบัติการพยาบาลและการพัฒนาวิชาชีพ แต่ความรู้เรื่องพัฒนาการของแนวคิดดังกล่าวในประเทศไทยยังมีเพียงน้อย บทความนี้มีวัตถุประสงค์เพื่อวิเคราะห์และสังเคราะห์มโนทัศน์ดังกล่าวโดยอิงกับวรรณกรรมที่มีอยู่ และเพื่อสำรวจปัจจัยที่มีอิทธิพลต่อเอกสิทธิ์แห่งวิชาชีพพยาบาลและเครื่องมือที่ใช้วัดมโนทัศน์ ข้อค้นพบทำให้ขอบเขต คุณลักษณะและแหล่งของเอกสิทธิ์แห่งวิชาชีพพยาบาลมีความชัดเจนมากขึ้น คำสำคัญ: เอกสิทธิ์ วิชาชีพพยาบาล